Agerdyrkningsstatistik af England. (Efter Farmers Magazine, 2det Bind. 1852.) - Jørgensen, B. S. (Tidsskrift for Landøkonomi, 2018)
Agerdyrkningsstatistik af England. (Efter Farmers Magazine, 2det Bind. 1852.)